Diseño estructural del pavimento flexible, en el mejoramiento del camino vecinal Rioja – Posic, utilizando el método Naasra, tramo del km. 00+000 al km. 6+090, distrito y provincia de Rioja, región San Martín - Macedo Vásquez, Frank Manuel (2014)
The problem that we approach in the present work of investigation, arises as need to improve the local way Rioja- Posic 1 plan of the km 00+000 to the km 6+090, District and PfóViñéé óf Riójá, Régióñ Sáñ Mái'tiñ. lnside the parameters of the improvement there arises as need the structural design of the flexible pavement, for what the author, tries to give solution to the need that one has pféséñtéél üsiñg ttié " Méttióél Nátióñál Assóéiátióñ óf Aüsti'áliáfl Státé Róáél Aüttiófitiés": Vialidad;s National Ássociation of the State of Áustraiia (NAASRA). The Method NAASRA, it relates the value support of the soil (CBR) that is obtained by means of tne stüaies óf mecnañiéS óf soils ana tne Jóaéls peífórmers o;; tné róáél-oéO, expressed in number of repetltions of Equlvaient Áxes (EE) that are obtalned by the studies of traffic; parameters that are fundamental for the determination of the thickness of the cap of road-bed or base, on which a superficial treatment will be placad he Monogelds and on it the sealed asphalt SLURRY SEAL of thickness 15m m. On having designad the flexible pavement by means of the method NAASRA, it shows his efficiency and economy for ways of low volume of traffic that opposite to the methods of design AASHTO and lnstitute of the Asphalt, which one has proceeded to his design with ends of comparison, prove with major costs that the method NAASRA; therefore we can affirm that the Method NAASRA is the most economic and of high performance in such a way that it will serve as contribution in the part of the investigation, as well as in the application for different futura projects and to be applied in different parts of our Region and of the éountry.